Understanding the molecular basis of vitiligo - a systematic review - Osuch, Magdalena; Gaik, Magdalena; Bogacz, Rafał; Uram, Ewa; Woźniak, Justyna; Womperski, Karol; Magda, Inga (Journal of Education, Health and Sport, 2023)
Introduction: Vitiligo is a systemic, chronic, hypopigmented dermatosis of unclear background. The disease is characterized by the selective loss or dysfunction of melanocytes. As a result we can observe various, well and non-squamous depigmentation areas of different size and shape. The pathogenesis of vitiligo is not fully understood, however, the current view is that the etiopathology of this disease is complex Purpose of the study: Current treatment models are often nonspecific, so it is important to understand the pathomechanism that can help with vitiligo lesions. It will also sensitize researchers to the search for new therapeutic options Material and methods: Collected scientific articles and guidelines available online of high substantive value. Expressions that were searched in databases: vitiligo, etiology, leptin, pathogenesis, reactive oxygen species, oxidative stress Results and conclusions: The scientific papers and researches cited in the article show that the major role is played by cellular stress and reactive oxygen forms, secondary inflammation or environmental factors. Cellular stress activates autoimmune and autoinflammatory mechanisms that destroy pigment cells. Therefore, there are probably even more mechanisms contributing to the development of vitiligo. Illness can affect the patient ’s quality of life. In recent years, there has been significant progress in understanding the pathogenesis of vitiligo. Effective treatment of vitiligo remains a difficult challenge for both scientists and dermatologists.